Subependymal heterotopia: a distinct neuronal migration disorder associated with epilepsy. - Raymond, A A (1994)
Subependymal heterotopia has recently been recognised as a cause of epilepsy, but the clinical and investigational features have not been fully described. The clinical, psychometric, imaging, and electroencephalographic features of 13 adult patients with subependymal heterotopia and epilepsy have been reviewed. Age at seizure onset ranged from 18 months to 20 years (median 13 years). There were significantly more female (12) than male (1) patients (p < 0.01). Diagnosis of subependymal heterotopia was made by MRI in 11 patients and CT in two. The heterotopic grey matter was nodular in 11 patients and diffuse in two; bilateral in eight and unilateral in five. There were significantly more patients with predominant right than left cerebral hemisphere involvement (p < 0.01). The most commonly involved site was the occipital horn of the lateral ventricles (10 of 13 patients). Eleven patients presented with partial epilepsy, 10 of whom also had secondarily generalised seizures. The clinical description of the seizures often suggested either an occipital (four patients) or temporal (five patients) onset. Two patients presented with absence attacks without clear focal features. Patients demonstrated normal early milestones (12 of 13 patients), including normal motor development (all patients) and average or above average intelligence (10 of 13 patients). An EEG examination showed normal background activity in all but two patients, one of whom had large intracranial haematomas. Epileptiform activity was usually widespread (10 of 13 patients) and in three patients, there was generalised 3-Hz spike and wave activity that had previously led to an erroneous diagnosis of concomitant primary generalised epilepsy. Onset of epilepsy in the second decade of life, normal developmental milestones and intelligence, and the finding of an overwhelming female preponderance differentiates subependymal heterotopia from other cortical dysgeneses. The female preponderance supports the importance of the X chromosome and sex steroids in the maturation and development of the cerebral cortex.